KATAKTERISTIK PENGEMBANGAN BERAS ANALOG BERBASIS PATI TALAS BENENG (Xhantosoma undipes) DAN JAGUNG (Zea mays) DENGAN PENAMBAHAN ALGINAT (Sargassum sp) - NUR IKHWANI LUBIS (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Most Indonesian people are very dependent on rice consumption to meet their daily carbohydrate needs. This results in a high level of rice consumption that exceeds its production level. This can have an impact on food security in Indonesia. The manufacture of analog rice from taro beneng starch, corn starch and the addition of alginate is possible as an alternative to rice, in addition analog rice can also be used as a high-fiber functional food. The purpose of this study was to determine the best formulation of the addition of alginate in the manufacture of analog rice based on from beneng taro and corn starches. The research employed a Completely Randomized Design (CRD) with a single factor alginate concentration consisting of four levels: 0%, 1%, 2%, and 3%. Each treatment was replicated three times, resulting in a total of 12 experimental units. The results revealed that the addition of 3% alginate produced the most favorable outcomes. Physical analysis showed that the optional formulation contined 197% rehydration power, and 111% sweeling power. Chemical analysis showed that the optimal formulation contained 0.86% fat, 2.14% protein, 13% moisture, 0.55% ash, 71.66% carbohydrates, and 6.25% dietary fiber. This fiber content contributes approximately 62.7% of the daily recommended fiber intake for the general population. From a sensory perspective, the 3% alginate formulation was also the most preferred by panelists, particularly in terms of appearance,odor, taste, and texture.Keywords: Analog rice, alginate taro starch, corn starch